PENGARUH HOMOGENITAS INDUSTRI DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP AUDIT REPORT LAG - Aqila Difa Putri; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This study aims to test the effect of client industry homogeneity and specialization industry auditor on audit report lag. In this study client industry homogeneity and specialization industry auditor variables act as independent variables while audit report lag act as the dependent variable. This study using nine variable controls such as Herfindahl index, type of industry, KAP Big 4, company size, extraordinary items, family ownership, financial leverage, complexity, and loss.             The sample that used in this study are manufacturing companies listed on the IDX in 2017 – 2020 that divided into before pandemic period (2017 – 2018) and on pandemic period (2019 – 2020). The sample selection is based on purposive sampling method. With all criteria and requirements determined, this study using 230 samples for before pandemic period and 258 samples for on pandemic period. The analytical method used in this research is multiple linear regression analysis.The result of this study found empirical evidence that simultaneously all variables affect negatively significant in audit report lag. Partially, this study has proved that client industry homogeneity and specialization industry auditor have a significant negative effect on audit report lag for 2017 – 2018. On the other hand, only client industry homogeneity that have a significant negative effect on audit report lag for 2019 – 2020, while the specialization industry auditor has a negative sign but insignificant on audit report lag.